Extrapolation Combined with Multigrid Method for Solving Finite Element Equations (Journal of Computational Mathematics, 2021)
An algorithm combining the MG method with two types of extrapolation is given for solving finite element equations with any initial triangulation. A high order approximation to the solution of PDEs can be obtained at the cost of order O(N) of computational work.